EVALUATION OF THE THIXOTROPY OF OIL-WELL CEMENTS USED FOR CEMENTING LOST CIRCULATION ZONES: EFFECT OF PLASTER AND BLAST FURNACE SLAG - T. Bouziani; Z. Makhloufi; A. Benmounah; M. Bédérina (Journal of Fundamental and Applied Sciences, 2015)
Cementing of oil and gas wells can be a very delicate operation. Among the concerns of service companies, during this operation are the nature and conditions of the formations in well. This is the case of cementing operations in southern Algeria, specifically on the fields of In-Amen, where the formations in lost zones are naturally weak and highly permeable. In these areas, drilling fluids (muds and cements) pumped will be, completely or partially lost, what we call "lost circulation". Thixotropic cements are useful to overcome lost circulation problems. They are characterized by a special rheological behavior, allowing it to plug lost zones when they are pumped. Our work aims to assess the thixotropy of cements perapred with two types of cement (class G Asland cement and CEM I 42.5 portland cement) with the plaster, using a viscometer with coaxial cylinder (couette type). Moreover, the effect of blast furnace slag (LHF) on the properties and thixotropic mixtures prepared was also studied. The results show that portland cement (available locally) can produce mixes with higher and more stable thixotropy than the class G cement (from importation), which is a practical and economical for cementing job operations in wells with loss zones. The results also show that the effect of LHF is positive, since in addition to his contribution to long term performances, especially the durability of hardened concrete, it improves the thixotropy of cement made of plaster.